Role of CCK1 receptor in metabolic benefits of intestinal enteropeptidase inhibition in mice - Kamal Albarazanji; Simon Amadeus Hinke; Cassandre Cavanaugh; Jianying Liu; Stephen Beck; Neetu Shukla; Rong Meng; George Ho; Raul C. Camacho; James Leonard; Andrea R. Nawrocki (PLoS ONE, 2025)
Enteropeptidase (EP; enterokinase) is a serine protease that regulates intestinal protein digestion by converting trypsinogen into active trypsin, and thus initiates activation of the pancreatic zymogen cascade. Chronic inhibition of EP and trypsin (EP/T) with camostat (Foipan, FOY-305) or its active metabolite (FOY-251) causes weight loss in obese mice by reducing intestinal protein absorption and suppression of food intake, however, the mechanisms leading to appetite suppression are not well understood. We tested the hypothesis that cholecystokinin (CCK) signaling mediates the anorectic effects of EP/T inhibition using a CCK1R inhibitor (loxiglumide) or CCK1R knockout (KO) mice. Acute treatment with loxiglumide was able to partially reverse FOY-251-induced gallbladder contraction and delayed gastric emptying in mice. Chronic co-administration of loxiglumide reversed FOY-251 mediated effects on food intake and metabolism in diet-induced obese (DIO) mice. Chronic dosing of FOY-251 caused similar reductions in food intake but greater weight loss in CCK1R KO mice compared to wildtype (WT) mice, primarily due to fat mass loss. Pair fed (PF) groups revealed food intake-dependent and -independent mechanisms of weight loss by FOY-251. Notably, FOY-251 treatment induced sustained weight loss, whereas body weight loss rebounded in PF animals. In CCKR1 KO mice, FOY-251 caused greater weight loss, and increased protein calorie loss relative to that in WT mice, while having no effect on glycemic control or FGF21. Hence, CCK1R-dependent and -independent mechanisms modulate the metabolic effects of EP/T inhibition and may play a role in maintaining weight loss by this mechanism.